Determining The Properties Of Green Laterized Concrete With Fly Ash For Sustainable Solid Waste Management - Ezekiel Babatunde Ogunbode; Ernest Ituma Egba; Olusegun Adeyemi Olaiju; Charles Nimibofa Johnson; Danboyi Joseph Amusuk; Yakubu Aminu Dodo (The Italian Association of Chemical Engineering, 2024)
Chemical Engineering Transactions, 63, 649-654.